Thyroid function studies in children of nephrotic syndrome - Dhanjal, Gurdeep Singh; Garg, Mani (International Journal of Contemporary Pediatrics, 2019)
Background: Nephrotic syndrome is a condition which is characterized by proteinuria, hypoproteinemia, hypercholesterolemia and significant edema. In children with nephrotic syndrome, it is probable to determine a hypothyroid state because of significant loss of thyroxine (T4), triiodothyronine (T3) in presence of proteinuria. The objectives of this study were to evaluate the level of serum free T3, free T4, and TSH in children with nephrotic syndrome and its correlation with healthy controls. Methods: A comparative study was carried out on total of 60 children (divided into two equal groups of 30 cases and 30 controls) in the age group of 1-18 years of either sex admitted to Department of Paediatrics. Maharishi Markandeshwar institute of Medical Sciences and Research. Mullana, Ambala, Haryana over a from January 2017 to September 2018. Serum free triiodothyronine (FT3), free thyroxine (FT4), thyroid stimulating hormone (TSH) were done in all 60 children and compared. Results: Among cases 18 (60%) were males and 12 (40%) were females. 63.4% of the cases were in the age group 1-10 years and 36.6% were in age group 11-18 years. Studied patients showed lowered FT3 and FT4 and raised TSH in comparison with normal values. Conclusions: Hypothyroidism should be actively sought for in children with nephrotic syndrome as it is a treatable complication.